Legal Regulation of Copyright of Works Created by Artificial Intelligence Creative Economy Actors: Pengaturan Hukum Hak Cipta Karya Ciptaan Artificial Intelligence Pelaku Ekonomi Kreatif - Nurjannah, Alifah (Annual Review of Legal Studies, 2024)
Artificial Intelligence, known as artificial intelligence, is a new breakthrough in the current digital era. Artificial Intelligence is considered capable of working and producing work like humans. This has had an impact on the Intellectual Property Rights sector, the existence of a work produced by Artificial Intelligence raises concerns regarding the urgency of protecting works. The purpose of this research is to analyze the legal protection of creations created by creative economy actors who use Artificial Intelligence if they adopt the United States Work Made for Hire Doctrine and/or the urgency of protecting creative economy creative works produced by Artificial Intelligence, including those Creations that can be protected by law. Copyright Act. This writing is normative juridical law writing using a qualitative approach method. The data obtained from this writing is from literature studies, namely books, scientific articles, interviews as supporting data and others. As well as document studies, namely based on statutory regulations. Data analysis uses qualitative descriptive research that is appropriately researched. The research results are: Protection of Creations resulting from Artificial Intelligence if adopting the Work Made for Hire Doctrine provides a solution that the subject of Creation results remains humans. In order to avoid a legal vacuum, Indonesia should be able to create implementing regulations by adopting the United States' Work Made for Hires concept. The urgency of creations produced by artificial intelligence can be included in the scope of creations protected by the UUHC, by paying attention to the principle of originality of creative works by creative creative actors who use applications and act as artificial intelligence programmers as a means of legal protection for their work.